2006
DOI: 10.1016/j.abb.2006.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Novel ZIP kinase isoform lacks leucine zipper

Abstract: Zipper-interacting protein kinase (ZIP kinase) has been thought to be involved in apoptosis and the C-terinal leucine zipper motif is important for its function. Recent studies have revealed that ZIP kinase also plays a role in regulating myosin phosphorylation. Here we found novel ZIP kinase isoform in which the C-terminal non-kinase domain containing a leucine zipper is eliminated (hZIPK-S). hZIPK-S binds to myosin phosphatase targeting subunit 1(MYPT1) similar to the long isoform (hZIPK-L). In addition, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…At least in ferrets, for which the protein sequence of Dlk is not known yet, Dlk was shown to colocalize with endogenous Par-4 on actin filaments in differentiated vascular smooth muscle cells (Vetterkind and Morgan, 2009). Even in human ARPE19 cells that have a much more pronounced microfilament system than the HeLa cells investigated (Shoval et al, 2007), an association of ZIPK with the microfilament system was observed (Takamoto et al, 2006). Taken together, these data suggest that in different species ZIPK protein recruitment to the microfilament system is achieved by different proteins: Although Par-4 functions as the predominant recruitment factor for Dlk in murine cells, human ZIPK may be targeted to microfilaments via different proteins, yet to be identified.…”
Section: Discussionmentioning
confidence: 89%
“…At least in ferrets, for which the protein sequence of Dlk is not known yet, Dlk was shown to colocalize with endogenous Par-4 on actin filaments in differentiated vascular smooth muscle cells (Vetterkind and Morgan, 2009). Even in human ARPE19 cells that have a much more pronounced microfilament system than the HeLa cells investigated (Shoval et al, 2007), an association of ZIPK with the microfilament system was observed (Takamoto et al, 2006). Taken together, these data suggest that in different species ZIPK protein recruitment to the microfilament system is achieved by different proteins: Although Par-4 functions as the predominant recruitment factor for Dlk in murine cells, human ZIPK may be targeted to microfilaments via different proteins, yet to be identified.…”
Section: Discussionmentioning
confidence: 89%
“…A mutation in the leucine zipper domain (V422A, V429A, and L436A) resulted in the drastic decrease in homodimerization and autophosphorylation of DAPK3 . Despite that, an isoform that lacks the leucine zipper domain retained the ability to bind myosin, indicating that myosin binding is mediated by the catalytic domain of DAPK3 …”
Section: Dapk Family Structurementioning
confidence: 99%
“…Others argued that the differences were species specific, and depended on whether the human or mouse/rat orthologs were used in these studies [6,14]. Since the latter possibility has not been studied in a direct manner, we have undertaken integrated bioinformatics and experimental analyses of ZIPK orthologs to test this hypothesis.…”
Section: Introductionmentioning
confidence: 99%